Communication Evaluation in the Maritime Security Policy in the Nias Archipelago Waters - Endyka Triono Dachi; Moch. Jurianto; Purwanto Purwanto (CV. Rayyan Dwi Bharata, 2023)
The Nias Islands are an area that is included in the Province of North Sumatra. Nias is an archipelago area surrounded by the Indonesian Ocean. The location of the Nias Islands which are on the border increases the risk of maritime threats that might occur in the Nias Islands. The research problem is how to evaluate communication in maritime security policies in the waters of the Nias Islands. The communication factor in policy implementation includes how to communicate the implementation of maritime security between agencies in maritime security in the territorial waters of the Nias Islands. This study aims to find out how the implementation of policies and efforts in maritime security in the waters of the Nias Islands, by analyzing communication in maritime security in the territorial waters of the Nias Islands. The research uses qualitative methods by collecting data through interviews, field observations and literature studies. The results of this study were processed using the Atlas.ti application. The results of the research show that there is synergy between government agencies in charge of maritime security in the Nias Islands, but there is a need to improve communication between these agencies. This form of communication is not only carried out to carry out maritime security in the territorial waters of the Nias Islands, but also aims to carry out monitoring of marine and fishery resources. Conducting sea patrols is an activity in the form of joint communication or coordination between agencies/institutions as well as a form of implementation of RI Minister of Defense No. 13 of 2014 concerning border area security policies. Communication is the key to creating synergy between ministries/agencies so that maritime security in the waters of the Nias Islands will run effectively and create a safe maritime environment. Evaluation of communication in maritime security policies in the waters of the Nias Islands shows that there are still communication limitations that cause operational constraints.